Serial „Westworld” — badanie etycznych granic „przesadnej przesady” - Marcin Telicki (Literatura i Kultura Popularna)
Based on the Westworld series created by the directorial duo of Lisa Joy and Jonathan Nolan, the author of the article discusses exaggeration as a diagnostic tool of contemporary culture. He analyses the image of a fantastic, post-humanist landscape in which the boundaries between reality and illusion and between humanity and its ideal imitation constructed by artificial intelligence are blurred. One of the most important points in the reflection on androids is the attitude to death and its ways of showing it. It leads not only to asking in-depth philosophical questions, but also to showing the literary and cultural series which Westworld is a part of. Finally, the series becomes a contribution to ethical considerations that are inscribed in the contexts of the most contemporary events and phenomena: the pandemic, the war in Ukraine or the development of AI. The threads of history and tradition, temporality and technological fantasies collide here, which makes the viewer and the reader reflect on the conditio humana.